Regaining the Constitutional Identity of the Finance Commission: A Daunting Task for the Thirteenth Commission - K.K. George K.K. Krishnakumar (CSES Working Paper No. 20, 2008)
In the context of the ongoing work of the Thirteenth Finance Commission, this paper examines the record of the recent Finance Commissions, with a view to suggesting how best the present Commission can and should assert itself and follow a new, independent approach. The paper argues that the Thirteenth Finance Commission has got to find its own track if it does not want to remain as a pale shadow of its constitutional self. It should ignore those terms of reference which are not mandated by the Constitution as well as those which have become obsolete with the onset of recession in the economy. If it has to gain acceptance of the States, it has got to follow an equidistant attitude towards the Centre and the States. The paper argues for substantially stepping up the resource flows from the Centre to the States in view of the severe fiscal crisis of the latter and consequent inability to meet their expenditure responsibilities bestowed on them by the Constitution. The paper finds that one of the terms of reference of the Commission setting the objective of balancing the revenue account of States and the Union government and generating surpluses for capital investment has become outdated with the onset of recession in the economy. The recession calls for abandoning fiscal conservatism and embarking on increased public expenditure to build physical and social overheads as also to provide social protection to the victims of recession. The paper recommends that the grants to States must be made unconditional and free from interference